Labor and the globalization of production : - Miberg, William (Palgrave Macmillan, 2004)
This book brings together the work of international economist, labor economists and sociologists in a far-reaching study of global production networks and the challenges they pose for developing country workers. A number of both empirical and theoretical questions are addressed and answers are provided by drawing on a variety of examples--from China to Mexico to South Africa to Eastern Europe. The studies show that globalized production creates a new set of challenges to economic development for entrepreneurs, workers, governments and international organizations.